2004
DOI: 10.1021/jp049936a
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Insights into the Sputtering of Ag{111} Induced by C60 and Ga Bombardment

Abstract: Molecular dynamics computer simulations have been utilized to compare the differences in the mechanism of sputtering of Ag{111} by kiloelectronvolt Ga and C 60 projectiles. The calculated kinetic energy distributions of Ag monomers and Ag 2 dimers compare favorably with experimental results. The damage caused by the C 60 particle left in the sample is less than the depth of material that the next impinging C 60 particle would remove, thus supporting the preliminary experimental observations that molecular dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
204
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(219 citation statements)
references
References 51 publications
10
204
2
2
Order By: Relevance
“…For comparison with recent MD computer simulations performed for the same projectiles impinging onto a°(111)°surface°of°an°ideal°Ag°single°crystal° [21],°the°MD data°have°been°included°in°Table°1.°First,°it°is°seen°that the measured yield variations are in qualitative agreement with the simulation. This is particularly true for the impact energy dependence observed under C 60 bombardment, where the experiment detects almost identical°ratios°as°predicted°from°the°simulations° [22].…”
Section: Total Yieldmentioning
confidence: 86%
See 2 more Smart Citations
“…For comparison with recent MD computer simulations performed for the same projectiles impinging onto a°(111)°surface°of°an°ideal°Ag°single°crystal° [21],°the°MD data°have°been°included°in°Table°1.°First,°it°is°seen°that the measured yield variations are in qualitative agreement with the simulation. This is particularly true for the impact energy dependence observed under C 60 bombardment, where the experiment detects almost identical°ratios°as°predicted°from°the°simulations° [22].…”
Section: Total Yieldmentioning
confidence: 86%
“…The spike model has traditionally been employed to interpret the response of metallic targets to cluster bombardment [20]. Instead, the emission mechanism is proposed to involve the quasi-free expansion of a super-critically heated subsurface volume.Recent molecular dynamics (MD) computer simulations show a largely different desorption process for isoenergetic Ga and C 60 bombardment [21,22]. For 15 keV Ga bombardment of Ag{111}, atomic motion is described by a classic collision cascade with a desorption yield of about 20 Ag atoms per incident Ga ϩ ion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that these enhanced yields are produced with a concomitant increase in surface damage, but the yield enhancement surpasses that of damage [32]. Many studies have combined to develop the now accepted idea that the lower penetration depth and overlapping collision cascades of the polyatomic primary ion deposit more energy in the surface region, thus leading to increased sputtering [33][34][35][36][37][38][39].…”
mentioning
confidence: 99%
“…A number of studies have shown that the sputtering efficiency of secondary ions is improved by increasing the mass of the primary particles. [1][2][3][4][5][6][7][8][9][10][11] Various methods have been reported for the formation of cluster ions as projectiles for cluster secondary ion mass spectrometry (SIMS). Blain et al produced cluster projectiles by 252 Cf-fission fragment-induced desorption.…”
mentioning
confidence: 99%